The complete CBT guide for anxiety - Shafran, Roz; Brosan, Lee; Cooper, Peter J. (London : Constable & Robinson, 2013)
A self-help guide to all the anxiety disorders: generalised anxiety disorder, health anxiety, panic, phobias, social anxiety, OCD. Edited by three leading CBT clinicians in the UK, it offers individual CBT-based treatments for a wide range of anxiety problems. Each individual treatment reflects current treatment in the UK for that anxiety disorder and is written by the clinician responsible for developing that treatment in the first place.
Common features of cognitive behavioural therapy for different anxiety problems -- Specific phobias -- Panic disorder -- Generalized anxiety disorder and worry -- Social phobia -- Health anxiety -- Obsessive compulsive disorder -- Post-traumatic stress disorder -- Tacking other problems and maintaining progress.
Includes bibliographical references (pages 429-433) and index.
Keywords: Kognitiv terapi; Ångest -- behandling; Anxiety disorders; Cognitive therapy; Anxiety disorders -- Treatment; Health and Wellbeing; Cognitive therapy